ENGINEERING STUDENTS DEALING WITH DISTRACTIONS: CHALLENGES, STRATEGIES, AND IMPLICATIONS - Bhanja, Pritish; Pranati Das; Sudarsan Sahoo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study dives into finding the varied distractions engineering students deal with in academic setups absorbed with increased digital engagement and rapid technological changes. Academic performance is seriously impacted due to these distractions that ranges from psychological stress to social media. In this paper, 120 engineering students from Centurion University, Bhubaneswar participated in a survey. The findings of the survey highlighted the main sources of distraction, institutional responses, and coping strategies of the students. The study also derives at a list of suggestions. Digital literacy, cognitive-behavioural techniques, and digital literacy are some essential techniques for a healthy digital habit that fosters focus and productivity.